Salt Marsh and Tidal Flat Area Distributions Along Three Estuaries - Kleinhans, Maarten G.; Douma, Harke; Addink, Elisabeth A.; Coumou, Laura; Deggeller, Tessa; Jentink, Robert; Paree, Edwin; Cleveringa, Jelmer (Frontiers in Marine Science, 2021)
Estuarine landscapes form through interactions between fluvio-coastal processes and ecological processes within the boundaries imposed by hard substrate layers and man-made dikes and dams. As estuaries are ecologically valuable areas, monitoring and quantification of trends in habitats is needed for objective comparison and management. However, datasets of tidal flat and saltmarsh habitats along entire estuaries are scarce. The objective was to compare trends of biogeomorphological areas and habitat transitions along three estuaries in the Netherlands and assess whether these are generally comparable or mainly determined by system-specific histories. We present data for these estuaries obtained by automated classification of false-color aerial imagery. The automated method allows objective mapping of entire estuaries at unprecedented resolution. The estuaries are dominated by subtidal areas and tidal flats. The tidal flats have similar area along the estuaries while saltmarsh area decreases. Collective lengths of ecologically important transitions between saltmarsh, low-energy tidal flats and water differ more between the estuaries. These variations are due to presence of mid-channel bars and shore-connected embayments. Saltmarsh area is mainly determined by the different formation and embankment histories of the estuaries, embayments and side-branches. Much of the past saltmarsh flanking the estuaries was lost due to past land reclamation. In one system, ecologically important low-energy tidal flats are reduced by a sudden decrease of tidal amplitude, causing increase of subtidal area at the cost of intertidal area. Large areas of high-energy tidal flats in one estuary remain unexplained. The automated method can be applied in other estuaries, provided that high-quality areal imagery is available. Extensions of the data to other estuaries would allow for system-scale trend comparison between estuaries of ecologically relevant biogeomorphological characteristics.